Investigation of Prohibitin Levels in Preeclampsia Cases: A Case Control Study from a Tertiary Hospital - Keser, Hasan Burak; Bulmuş, Funda Gülcü; Kavak, Salih; Kavak, Ebru Çelik (Ankara Şehir Hastanesi, 2025)
Introductıon: To evaluate the relationship between the effects of prohibitin at the cellular level and the pathophysiology of preeclampsia. Methods: This study included a total of 120 patients who presented to our clinic at 20–41 weeks of gestation. The participants were divided into three groups: 40 pregnant women with preeclampsia with severe features, 40 pregnant women with preeclampsia, and 40 healthy pregnant women. To measure serum prohibitin levels, 10 cc of venous blood was collected from each participant, and comparisons were made between the groups. Results: Serum prohibitin levels were significantly higher in pregnant women with preeclampsia with severe features and preeclampsia compared to the control group (p
Keywords: One Health; Tek Sağlık